Una hermenéutica de la cruz de Jesús desde el "realismo político". (2016)
In the context of a Christianity affected by the anthropological turn and the rethinking of the question by the human being and his being/be in the world in the perspective of humanization-dehumanization of existence, the logic of social justice-injustice and the Faith paradox facing the pain and human misery makes sense to ask about the experience of faith in the Lord crucified-risen-resuscitated. The theology of the cross –staurology inside the systematic theology–, which is part of a critical theological tradition criticism and also, humanizing and hopeful, is an essential point to face questions and paradoxes of latemodern Western Christianity. The cross evokes provocation, insanity, paradox, suffering, curse, anxiety, anamnetic memory; but also hope and criterion of discernment of God's answer to the human condition. It symbolizes the ridicule and torture of Christ, the depth of suffering of those who in the eyes of Romans and Jews died as a rejected, cursed by God and blasphemous. It condenses the image of that triumphant and victorious Christianity, which in the imagination of the great German poet Friedrich von Schiller is displayed as "religion of the cross", motif of thrones and empires that often in the Middle Ages caused the rejection and death. But the very symbol of the cross, the sign of the cross and the crucifix also symbolize faith and worship of marginalized and clandestine Christian communities, the praying look and attitude, the Christian piety and the hope of salvation beyond the pain and human finitude.